A dense residual U-net for multiple sclerosis lesions segmentation from multi-sequence 3D MR images. (February 2023) - Sarica, Beytullah; Seker, Dursun Zafer; Bayram, Bulent
Abstract: Multiple Sclerosis (MS) is an autoimmune disease that causes brain and spinal cord lesions, which magnetic resonance imaging (MRI) can detect and characterize. Recently, deep learning methods have achieved remarkable results in the automated segmentation of MS lesions from MRI data. Hence, this study proposes a novel dense residual U-Net model that combines attention gate (AG), efficient channel attention (ECA), and Atrous Spatial Pyramid Pooling (ASPP) to enhance the performance of the automatic MS lesion segmentation using 3D MRI sequences. First, convolution layers in each block of the U-Net architecture are replaced by residual blocks and connected densely. Then, AGs are exploited to capture salient features passed through the skip connections. The ECA module is appended at the end of each residual block and each downsampling block of U-Net. Later, the bottleneck of U-Net is replaced with the ASSP module to extract multi-scale contextual information. Furthermore, 3D MR images of Fluid Attenuated Inversion Recovery (FLAIR), T1-weighted (T1-w), and T2-weighted (T2-w) are exploited jointly to perform better MS lesion segmentation. The proposed model is validated on the publicly available ISBI2015 and MSSEG2016 challenge datasets. This model produced an ISBI score of 92.75, a mean Dice score of 66.88%, a mean positive predictive value (PPV) of 86.50%, and a mean lesion-wise true positive rate (LTPR) of 60.64% on the ISBI2015 testing set. Also, it achieved a mean Dice score of 67.27%, a mean PPV of 65.19%, and a mean sensitivity of 74.40% on the MSSEG2016 testing set. The results show that the proposed model performs better than the results of some experts and some of the other state-of-the-art methods realized related to this particular subject. Specifically, the best Dice score and the best LTPR are obtained on the ISBI2015 testing set by using the proposed model to segment MS lesions. Highlights: A novel encoder-decoder architecture based on the U-Net architecture with dense connections, residual blocks, AG, ECA, and ASPP is proposed. ISBI2015 and MSSEG2016 datasets were employed to validate the proposed model's segmentation performance, generalization, and robustness. Different MRI sequences, such as FLAIR, T1-w, and T2-w, were incorporated into the proposed model to obtain more features related to MS lesions. To use contextual information in all plane directions, 2D slices extracted from the axial, sagittal, and coronal planes of each 3D MRI were used. A 3D binary mask reconstruction approach was presented to generate a 3D output binary mask from predicted 2D slices of each plane.